Design of a Lora-Based Early Warning System for Watersheed Flood Disaster Using Data Logging - Prastyo Tri Sumargono; Kartiko Ardi Widodo; F. Yudi Limpraptono (Fakultas Teknik Universitas Bhayangkara, 2025)
Flood disasters in river basins often occur due to high rainfall, poor river management, and poor land use. To minimize the impact, this study designed a LoRa (Long Range)-based early warning system in watersheds for efficient long-distance data transmission and reception. This system integrates ultrasonic sensors to monitor water level, Arduino Uno microcontrollers and NodeMCU ESP8266 for data processing, LoRa as a communication medium, and a web server for real-time data display, on the web server the water level is divided into 3 statuses, namely Safe (0-20CM), Beware (21-30CM), and Danger (>31CM). An email-based early warning feature is also used to alert the Hazard status when the water level >31 CM. Tests show that this system has a high level of accuracy in water level readings of up to 50 cm and data transmission up to a distance of 1,000 meters in optimal conditions. With the efficiency of communication and real-time analysis, this system can improve community preparedness for flood disasters.